Tumor-associated neutrophil precursors impair homologous DNA repair and promote sensitivity to PARP inhibition - Siddhartha Mukherjee; Cindy Garda; Letizia Boffa; Angela Rita Elia; Matteo Massara; Maria Teresa Balia; Daniela Brina; Simone Mosole; Anna Campagnari; Giada Andrea Cassanmagnago; Andrea Rinaldi; Giacomo Lazzaroni; et al. (Nature Communications)
Abstract Tumor evolution is one of the major mechanisms responsible for acquiring therapy-resistant and more aggressive cancer clones. Whether the tumor microenvironment through immune-mediated mechanisms might promote the development of more aggressive cancer types is crucial for the identification of additional therapeutic opportunities. Here, we identify a subset of tumor-associated neutrophils, defined as tumor-associated neutrophil precursors (PreNeu). These PreNeu are enriched in highly proliferative hormone-dependent breast cancers and impair DNA repair capacity. Mechanistically, succinate secreted by tumor-associated PreNeu inhibits homologous recombination, promoting error-prone DNA repair through non-homologous end-joining regulated by PARP-1. Consequently, breast cancer cells acquire genomic instability promoting tumor editing and progression. Selective inhibition of these pathways induces increased tumor cell killing in vitro and in vivo. Tumor-associated PreNeu score correlates with copy number alterations in highly proliferative hormone-dependent tumors from breast cancer patients. Treatment with PARP-1 inhibitors counteract the pro-tumoral effect of these neutrophils and synergize with endocrine therapy.